2023
DOI: 10.1039/d3tc01969a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in multicolor electrochromic devices based on inorganic materials

Abstract: With the rapid development of optoelectronic fields, electrochromic (EC) devices with multicolor tunability have received remarkable attention and have shown attractive potential for use in emerging electronic papers/billboards, see-through displays,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 111 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…One promising application of supercapacitors lies within the electric vehicle sector, where they can complement traditional batteries. 5–8 By doing so, they improve vehicle acceleration performance, enhance range, optimize energy efficiency, and reduce fuel consumption. 9–11 In renewable energy, particularly solar and wind power generation, supercapacitors can effectively store surplus energy and balance supply-demand fluctuations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One promising application of supercapacitors lies within the electric vehicle sector, where they can complement traditional batteries. 5–8 By doing so, they improve vehicle acceleration performance, enhance range, optimize energy efficiency, and reduce fuel consumption. 9–11 In renewable energy, particularly solar and wind power generation, supercapacitors can effectively store surplus energy and balance supply-demand fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…9–11 In renewable energy, particularly solar and wind power generation, supercapacitors can effectively store surplus energy and balance supply-demand fluctuations. 12–15 In the smart grid context, supercapacitors can act as energy buffers, stabilizing power supply and promoting grid resilience. 16–19 In essence, supercapacitors offer a sustainable approach to energy storage, reducing carbon footprints and fostering a greener future.…”
Section: Introductionmentioning
confidence: 99%
“…Thermochromic materials are a kind of smart materials that show controllable obvious color changes in response to temperature, 1 and these have promising applications in thermometer pigments, heat warning paintings, 2 thermal response smart windows, 3,4 heat-sensitive anticounterfeiting, 5 environment-adaptive military camouflage, 6 and energy harvesting. 7,8 Themochromic materials can be roughly divided into two parts: organic and inorganic, based on their compositions.…”
Section: Introductionmentioning
confidence: 99%
“…14 Compared with organic electrochromic materials represented by organic small molecules, 15,16 and conductive polymers, 3,17,18 inorganic electrochromic materials are more suitable for practical applications due to their excellent chemical stability and long-term durability. 19–21 Since Deb et al reported the first instance of inorganic electrochromic materials and devices when studying amorphous and crystalline tungsten oxide at Cyanamid Corporation in 1969, inorganic electrochromic materials have experienced rapid development over the past 50 years. 22,23 The coloring mechanism of inorganic electrochromic materials represented by transition metal oxides (TMOs) and Prussian blue (PB) and its analogs (PBAs) is related to the presence of unpaired electrons in the d orbital.…”
Section: Introductionmentioning
confidence: 99%